Analisis Pengiriman Data Di Daerah Terpencil Menggunakan Dua Node Bergerak Berbasis Delay Tolerant Network (DTN) Dengan Algoritme Flooding - Bella Aulia Rahmataufany; Rakhmadhany Primananda; Aswin Suharsono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Abstract With the development of information technology today, the exchange of data and information becomes a necessity, not least in remote areas. Remote areas have their own characteristics, such as geographical conditions difficult to reach by the network. Due to these circumstances the exchange of information becomes a difficult thing to do. Delay tolerant network (DTN) is a network that can operate at great distances. Internet connections can be present in backward areas though indirectly. Delay tolerant networks can also transmit data packets on networks that have difficult terrain or not continuously available connections. The delay tolerant network architecture implements the method of saving and forwarding messages by using a new protocol layer called bundle layer. One developer of delay tolerant networks is IBR-DTN. IBR-DTN is an efficient software for embedded systems. There are several previous studies related to data transmission based on tolerable network tolerance. However, in this study researchers used the flooding algorithm to conduct research on the analysis of data transmission in remote areas using two moving nodes based on toler tolerance network with flooding algorithm. In this study used two moving nodes to view the broadcast process of the routing flooding algorithm. The two nodes are used to see the effect on time, which is required when sending data from village to city. There are three tests for predefined scenarios, including data transmission with two moving nodes, data transmission with one node moving disconnected, sending data using multiple files. The test results obtained are simulations built to make data transmission with the state there are two moving nodes or there is only one moving node. Despite having longer required data transfer, if the data is small (not more than 5 files, with a size of 1 to 5 Mb) with one intermediate node, the probability of data reaching the destination is smaller than the two moving nodes.